2022
DOI: 10.1111/nuf.12828
|View full text |Cite
|
Sign up to set email alerts
|

The association of mindfulness with professional quality of life and negative emotional states among critical care nurses during COVID‐19 pandemic

Abstract: Background: The recent coronavirus disease 2019 (COVID-19) pandemic has imposed severe psychological pressure on nurses. Mindfulness has been shown to be effective in improving professional quality of life (ProQOL) and reducing psychological distress in a wide range of populations and contexts. However, its role in supporting critical care nurses during the outbreak of COVID-19 has yet to be established. Purpose: This study explores the relationship of mindfulness with negative emotional states and ProQOL amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The development of CF can weaken clinical nurses’ ability to feel sympathy and empathy at work, therefore hindering the provision of safe, competent, and ethical care [ 5 , 16 ]. Previous studies showed that a large number of nurses were deeply troubled by diverse negative physiological and psychological symptoms related to CF, such as headaches, insomnia, musculoskeletal disorders, depression and professional helplessness [ 17 , 18 , 19 , 20 ]. In addition, clinical nurses who suffer from CF can not only manifest low job satisfaction and work engagement, but also show poor job performance and increased medical errors [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of CF can weaken clinical nurses’ ability to feel sympathy and empathy at work, therefore hindering the provision of safe, competent, and ethical care [ 5 , 16 ]. Previous studies showed that a large number of nurses were deeply troubled by diverse negative physiological and psychological symptoms related to CF, such as headaches, insomnia, musculoskeletal disorders, depression and professional helplessness [ 17 , 18 , 19 , 20 ]. In addition, clinical nurses who suffer from CF can not only manifest low job satisfaction and work engagement, but also show poor job performance and increased medical errors [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,14,15 We extended this theory to include negative emotional states of stress, anxiety, and depression along with demographic, and work characteristics related to empathy and ethical sensitivity based on literature that supports these relationships. [20][21][22][23]…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…These emotions can arise from a sense of responsibility, worry, and concern for the well-being of the person being cared for. 21 When we experience stress and anxiety in caring relationships, they can have significant impacts on our ability to provide care. For example, they can lead to burnout, reduced quality of care, and even harm to the person being cared for.…”
Section: Introductionmentioning
confidence: 99%
“…Working in an intensive care unit (ICU) introduces a real-life stressor that is difficult to change due to the nature of the work [ 1 , 2 ]. The critical care environment is difficult and uncertain under normal conditions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%